Evaluation of bio-psycho-social frailty in older persons on the territory: the method and the experience of the “Medesano Health House” - Gelmini, Giovanni; Pettenati, Paola; Baratta, Stefania; Loss, Maria Grazia; Lunghi, Mario; Veronese, Nicola (Acta Biomedica Atenei Parmensis, 2020)
Background and aim of the work: Frailty in older people is a situation of risk of dependency caused by many factors. On this consideration, the Medesano city started a survey on the condition of fragility of people >75 aimed at building a monitoring system for timely interventions on the factors of risk and implementation of measures for preventing dependency. Methods: The survey was conducted jointly by the family doctor and the social worker in the City. The multidimensional assessment considered logistic and housing conditions, disease, medications, basic and instumental acitvities of daily living, neurological and psycological conditions. Results: The survey included 761 older people, with a following definition of condition and levels of frailty both at social (loneliness, lack of supporting network, etc..) and health level (complexity of the regimen, high and / or severe comorbidity) was planned from the beginning as the basis on which developing a continuous in time monitoring program for assessing the frailty, for a early taking in charge by Health and Welfare services, boosting integrated health and welfare interventions and promoting networks of solidarity and sociality. Conclusion: The data seem to confirm that the methodology used is sufficiently adequate to intercept frailty in > 75 years unknown to social services indicating that the monitoring on the functionality of the subjects obtained from the surveys by the General Practitioners could be deemed as a privileged way for a survey on large populations. After the survey was activated continuous monitoring of patients with social and clinical frailty.